Aulas práticas na disciplina de química nas propostas do governo do estado de São Paulo: entraves predominantes, percepções e encaminhamentos - Ramos, Lilian Gomes [UNIFESP] (2020)
This work shows that the lack of articulation of curriculum content in the theory-practice-experience triad has a small contribution to the knowledge of a certain historically constituted scientific area, requiring institutions anddidactic material creators, care and sensitivities in the selection and inclusion of laboratory experiences in books or booklets that contain a specific content. When consulting the content and observing the recurrences of teacher complaints in some scientific works regarding the Student Notebooks prepared by the State of São Paulo for the teaching of Chemistry, more specifically for the development of classroom experiments in this discipline, it is understood that such framework is presented as a research problem to be developed. Therefore, the objective of this research was to investigate the main problems and challenges to teacher of the São Paulo state network (Santo André Teaching Directorate), to elaborate referrals regarding the adequacy of the “Notebook of the Student” proposals to the needs of the teachers, as well as the analysis of these proposals, regarding the development of practical classes in the discipline of Chemistry, especially when using these Notebooks, specific to the São Paulo State Government for the area. This work was developed by qualitative research of exploratory nature, using as questionnaire material of data collection with the elaboration of script of semi-structured questions and informal interview. The literature review will have as a preliminary axis the contributions of authors, which start from the prerogative of the difficulties in teaching Chemistry also due to the little use of practical activities and the criticism that underestimates the practical classes in the scope of little or no experimentation in conjunction with the experiences or experiences of the communities. It is envisaged that there is clarity as to the teaching justifications for the realization or not of practical classes, whether based on demonstration or experiments in which the student is the protagonist and also, adapt the proposals of the student's notebook promoting a greater possibility of applying them.